2021
DOI: 10.1155/2021/8810517
|View full text |Cite
|
Sign up to set email alerts
|

miR-301b-3p Regulates Breast Cancer Cell Proliferation, Migration, and Invasion by Targeting NR3C2

Abstract: Objectives. Breast cancer is the most common malignant tumor among females, and miRNAs have been reported to play an important regulatory role in breast cancer progression. This study aimed to explore the function and underlying molecular mechanism of miR-301b-3p in breast cancer. Methods. Differential analysis and survival analysis were performed based on the data accessed from the TCGA-BRCA dataset for identification of the target miRNA. Bioinformatics analysis was conducted to predict the downstream target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Fan and colleagues demonstrated that miR-301b-3p was significantly elevated in breast cancer. Furthermore, miR-301b-3p accelerated cell proliferation, migration, and invasion through binding to NR3C2 18 . Also, Liu and coworkers revealed that miR-301b-3p promoted lung adenocarcinoma malignancy through suppressing DLC1 expression [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fan and colleagues demonstrated that miR-301b-3p was significantly elevated in breast cancer. Furthermore, miR-301b-3p accelerated cell proliferation, migration, and invasion through binding to NR3C2 18 . Also, Liu and coworkers revealed that miR-301b-3p promoted lung adenocarcinoma malignancy through suppressing DLC1 expression [19].…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that miR-140-3p attenuated CRC progression and liver metastasis via BCL9 transcription coactivator (BCL9) and BCL2 apoptosis regulator (BCL2) [ 17 ]. Previous studies identified that miR-301b-3p was associated with the development of several carcinomas, such as breast cancer [ 18 ], lung adenocarcinoma [ 19 ], gastric cancer [ 20 ], and hepatocellular carcinoma [ 21 ]. However, the potential functions and possible mechanisms of miR-301b-3p in CRC were largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al. found that the expression of NR3C2 was downregulated in breast cancer ( 52 ). High expression of NR3C2 was significantly correlated with prolonged OS ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…High expression of NR3C2 was significantly correlated with prolonged OS ( 53 ). Overexpression NR3C2 could repress the proliferation, migration, and invasion for breast cancer and hepatocellular carcinoma ( 52 , 54 ). Consistent with previous studies, NR3C2 was decreased in patients with KIRC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in various countries have shown that NR3C2 acted as a tumor suppressor gene in a variety of tumors. The NR3C2 gene can inhibit tumor cell proliferation, migration and invasion [40][41][42][43] . In addition, the NR3C2 gene is closely associated with the prognostic status of patients with BRCA: the less it is expressed, the worse the prognosis [39][40] .…”
Section: Discussionmentioning
confidence: 99%